Az iskolai kultúra összetevőinek kísérleti vizsgálata - Prihoda, Gábor; Karsai, István; Kövécs, Tünde (Magyar Pedagógia, 2017)
During the spring of 2015, we conducted cross-sectional field research using the qualitative approach in eight Hungarian elementary schools with the aim of exploring sociocultural elements that define everyday life in public education institutions. During the research, 53 hours of audio material were collected and processed, providing the sample for the analysis. The results of the study were reached through content analysis, especially interpretative phenomenological analysis (IPA) and the interpretative approach used in anthropology. The evaluation of the school culture assessment results mapped out the underlying structure, called a School Culture Map, which drew attention to a range of social activities. Our assumption suggests that the elements of school culture – values, norms, and symbols identifiable from phenomena and content – become relevant when connected to social activities and interaction between adults and school children. In our analysis, we illustrate this connection by applying the model of first-generation activity theory. The experimental application of this theory was suitable to shed light on complex and apparently contradictory school trends and phenomena. Furthermore, it contributes to the understanding of the values, norms, and symbols of school culture, and their effects and interrelationships on everyday school life.